2022
DOI: 10.1007/s00240-022-01323-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for concomitant positive midstream urine culture in patients presenting with symptomatic ureterolithiasis

Abstract: In patients with symptomatic ureterolithiasis, immediate treatment of concomitant urinary tract infection (UTI) may prevent sepsis. However, urine cultures require at least 24 h to confirm or exclude UTI, and therefore, clinical variables may help to identify patients who require immediate empirical broad-spectrum antibiotics and surgical intervention. Therefore, we divided a consecutive cohort of 705 patients diagnosed with symptomatic ureterolithiasis at a single institution between 2011 and 2017 into a trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As the result of the gold standard urine culture will take 24 h at the earliest, which patient can go to sepsis will depend on the clinician’s evaluation in the light of clinical, laboratory and imaging studies. In patients with high acute phase reactants, fever, kidney failure, and pyuria and nitrite positivity in urine analysis, urine culture should be taken and broad-spectrum empirical antibiotic treatment should be started, and antibiotic changes should be made if necessary, according to the urine culture results [ 27 ]. Definitive treatment should be left after clinical stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…As the result of the gold standard urine culture will take 24 h at the earliest, which patient can go to sepsis will depend on the clinician’s evaluation in the light of clinical, laboratory and imaging studies. In patients with high acute phase reactants, fever, kidney failure, and pyuria and nitrite positivity in urine analysis, urine culture should be taken and broad-spectrum empirical antibiotic treatment should be started, and antibiotic changes should be made if necessary, according to the urine culture results [ 27 ]. Definitive treatment should be left after clinical stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…These scoring systems, which have shown improvements in mortality differentiation, calibration, and predictive ability, are recommended to identify and predict the prognosis of patients with sepsis [41,42]. To meet the demands of clinical practice and fully understand the progression of sepsis, numerous researchers have integrated various biomarkers to predict mortality in patients with sepsis [43,44], with some studies combining biomarkers with scoring systems to do so. For example, Rijhwani et al [45] found that combining biomarkers (lactate, C-reactive protein, procalcitonin) with the qSOFA score predicted the 28-day mortality of patients with sepsis better than using the qSOFA alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several previous studies investigated the association of perirenal stranding with urinary tract infections and the impact on outcomes after different therapeutic approaches. Indeed, studies reported conflicting findings about the association of perirenal stranding with the risk of concomitant urinary tract infection [ 12 , 13 ]. Authors reported an increased risk of infection after ureterorenoscopic stone removal or after ureteral stent insertion in patients with ureteral stone and perirenal stranding [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%